Lichen planus pigmentosus masquerading as seborrheic melanosis: A case report - Jayati Shailesh Dave; Atul Dongre; Sunanda Arun Mahajan (Wolters Kluwer Medknow Publications, 2023)
Lichen planus pigmentosus is a macular variant of lichen planus commonly affecting photo-exposed areas. A 45-year-old female presented with asymptomatic blackish pigmentation on the both naso-labial folds, alar grooves, angle of mouth, lower lip, medial canthus, and eyelids since 8 years. Dermoscopy of these pigmented lesions revealed non-uniform accentuation of pseudoreticular pattern with dark brown dots and globules in arcuate and incomplete reticular fashion suggestive of lichen planus pigmentosus. Biopsy from the lesion showed perivascular infiltrate with heavily pigmented melanophages in the upper dermis. Based on clinico-pathological correlation and dermoscopic features, diagnosis of lichen planus pigmentosus was made.